EFFECTS OF GLOBALISATION ON EMPLOYMENT RELATIONS WITHIN THE FILM INDUSTRY IN SOUTH AFRICA - Mpabanga, Zanele L.; Ukpere, Wilfred Isioma (Annals of Spiru Haret University. Economic Series, 2022)
Globalisation has been perceived as the integration and spread of information, processes and technology across organisations and nations. It has accelerated transformation and change in organisations, with the effect of strengthening or, as the case may be, weakening employment relations within organisations. Globalisation has been characterised by a rise in the use of casual employees, decentralisation and continuous advancement in technology, which ultimately affects employment relations. Therefore, this paper sets to explore the effects of globalisation on employment relations in South Africa’s film industry. The current investigation adopted a qualitative research approach, which was carried out in an organisation within the film industry in the city of Johannesburg, South Africa. Purposive sampling was used to collect data from ten employees at various levels in the organisation. Data was obtained by means of semi-structured face-to-face interviews with the research participants. The findings revealed that the effects of globalisation are twofold, as it has both positive and negative effects on organisations. From a positive perspective, it was found that globalisation has helped to promote inclusive workplaces, effectively manage tensions and conflict in the workplace, and improve communication between parties in the employment relationship. Furthermore, it was discovered that interactions between management and employees have increased since globalisation. Conversely, the current findings uncovered that there are increasing tensions in the employment relationship. There is also evidence of less training to workers in the film industry. The findings further revealed that using casual employees in the film industry has increased, and many of them are confronted with several challenges, as they do not get the same benefits that their counterparts in permanent employment receive. Hence, generally, this paper’s outcome could be used in organisations to address some of the negative effects of globalisation in respect of relationships in the workplace, particularly in the film industryg.